Accuracy of an oscillometric blood pressure monitor in anesthetized pigs. (October 2018) - Reed, Rachel; Barletta, Michele; Grimes, Janet; Mumaw, Jennifer; Park, Hea Jin; Giguère, Steeve; Azain, Michael; Fang, Xi; Quandt, Jane
The purpose of this study is to evaluate the accuracy of an oscillometric blood pressure monitor in anesthetized pigs. Invasive blood pressure (IBP) and noninvasive blood pressure (NIBP) measurements were taken using a DRE Waveline Pro multiparameter monitor at four different time points in 17 pigs undergoing injectable anesthesia. NIBP measurements were taken on both the thoracic and pelvic limbs. Bland Altman analysis was used to assess agreement between methods and a linear mixed-effects model was used to evaluate the effect of cuff position and blood pressure on bias. Invasive systolic arterial pressure (SAP) ranged between 112 and 161 mmHg (mean ± SD: 138.8 ± 13.3; median: 139.5). Invasive diastolic arterial pressure (DAP) ranged between 60 and 104 mmHg (mean ± SD: 86.0 ± 9.1; median: 87.0). Invasive mean arterial pressure (MAP) ranged between 79 and 121 mmHg (mean ± SD: 103.2 ± 9.3; median 103.0). Only the diastolic and mean measurements obtained from the pelvic limb met criteria outlined by the American College of Internal Medicine for required accuracy of NIBP monitors. Bias was significantly higher in the thoracic limb in comparison to the pelvic limb and was significantly higher at blood pressures above median. In general, NIBP measurements underestimated IBP measurements. In conclusion, the use of the DRE Waveline Pro to assess NIBP in anesthetized pigs may be useful in monitoring trends in mean and diastolic blood pressure and is most accurate when used on the pelvic limb.